Correlation of Disturbed Sleep and Cancer Stress. Issue 1 (2nd January 2017) - Vander Wal, Gregory S.; Lichstein, Kenneth L.; Perkins, Cynthia K.
Abstract : To illuminate the course of insomnia in the presence of an acute comorbidity, we examined the association between insomnia severity and breast cancer symptom severity over time and determined if this association varies with insomnia history and presleep arousal. Twenty-nine newly diagnosed breast cancer patients, who also exhibited insomnia, completed sleep diary and cancer symptom severity questionnaires every other week (total of 28 days) over 7 weeks, as well as baseline and postobservation measures. Participants were defined as having insomnia prior to cancer (IPC) or insomnia secondary to cancer (ISC) based on precancer sleep status. Insomnia and cancer symptom severity were strongly correlated at baseline but significantly declined over the evaluation period. Among ISC individuals, there was an association between sleep severity and cancer severity at baseline but not 7 weeks later. IPC individuals showed a consistent pattern of no significant association between sleep severity and cancer symptom severity. IPC had higher levels of cognitive presleep arousal than ISC. The current study documented the evolution of the relation between insomnia and breast cancer symptom severity over time and identified factors (premorbid insomnia and presleep hyperarousal) that may influence this association.